Experiences and needs of Chinese women after a stillbirth: a qualitative phenomenological study - Xu Zhang; Li Chen; Yueming Zhang; Jia Shi; Yan Zhu; Qiyu Qian; Feizhou Jiang; Guangping Chu; Li Pu (BMJ Open, 2024)
Objectives We aimed to explore the lived experiences and needs of women after a recent stillbirth event.Design Qualitative phenomenological study.Setting The current study was conducted in a tertiary obstetric hospital in East China between 25 January 2024 and 29 March 2024.Participants 14 women having experienced a stillbirth within the last 6 months.Results Researchers agreed on four key themes including individual variations in emotional reaction and recovery, physical recovery and concerns about future pregnancies, the critical role of social support systems and variations in perceptions of stillbirth as the death of a fetus versus a human being, along with related mourning rituals. These themes collectively highlight the multifaceted nature of the stillbirth experience, underscoring the complex interplay between personal, cultural and medical factors that shape women’s emotional and physical responses.Conclusions Post-stillbirth experiences among Chinese women are deeply individualised and influenced by a complex interplay of personal emotions, cultural contexts and medical interactions. It is imperative for healthcare systems to implement tailored care strategies beyond standard protocols to proactively address their varied emotional landscapes and physical concerns with an enhanced awareness of cultural sensitivities. Specialised training for healthcare providers should be devised to recognise and respond to the unique grief processes. Comprehensive support systems should be established to significantly enhance the recovery journey by providing essential resources and community connections.